(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Present paper deals with some ethno medicinal uses of some important crops vegetable plant species and their uses, by the tribal of Umarkhed Tahsil, in Yavatmal district of Maharashtra. This region is inhibited by tribal communities like Banjara, Gond, Mang, Paradhi etc. The ethno Botanical information on plants viz., Botanical name, family, local name, plant part used and mode of administration is enumerated.